PENGARUH PENAMBAHAN NATRIUM HIPOKLORIT (NaOCl) TERHADAP MIKROBA PADA AIR LIMBAH DENGAN METODE MEMBRANE FILTER - Riani, Pevi; Hidayana, Hijratul (Politeknik ATI Padang, 2023)
This research was conducted to determine the effect of adding sodium hypochlorite (NaOCl) on the number of E. coli and Total Coliform bacterial colonies in industrial wastewater using membrane filters. The prepared wastewater is added with NaOCl with concentration variations 0 ; 0.5 ; 1 ; 1.5 ; 2 ; 3 ; 4 ; 5 ppm. The vacuum pump and filter membrane are placed in laminar air flow and the filtration process is carried out. The filtered membrane paper was placed into a petri dish containing CCA agar media and incubated for 24-48 hours at a temperature of 35oC with the petri dish upside down. Reddish pink colonies indicate colonies of Coliform bacteria, while dark blue or violet colonies are colonies of Escherichia coli bacteria. The results showed that the number of E. coli bacteria at NaOCl concentrations of 0 ppm to 5 ppm was 0 cfu/100 mL and Total Coliform was obtained at NaOCl concentrations of 0 ; 0,5 ; 1 ; 1,5 ; 2 ; 3 ; 4 dan 5 ppm is cannot be Calculated, 96 ; 74 ; 53 ; 31 ; 19 ; 3 and 0 cfu/100 mL.